Aspects that influence the self-care of patients living with human immunodeficiency virus - Alencar, Rubia Aguiar [UNESP]; Henrique Parenti, Ana Beatriz [UNESP]; Lopes, Camila de Carvalho [UNESP]; Ramos, Fabiana Tome [UNESP]; Ciosak, Suely Itsuko (Univ Sao Paulo, Escola De Enfermagem De Ribeirao Preto, 2019)
Objective: to analyze aspects related to the increase or decrease of self-care in patients living with human immunodeficiency virus treated in a specialized outpatient service. Method: analytical cross-sectional study with 135 patients aged 18 and over, of both sexes, who are followed up on the service. The independent variables and outcomes were collected from the nursing consultation instrument, whose theoretical reference is the Orem's Theory. The data were analyzed by parametric approach. Relationships or differences were considered significant if p<0.05. The analysis was done with SPSS v21.0 software. Results: most participants were male (56.3%), with a mean age of 42.1 years. Patients who needed to conceal the diagnosis had less self-care (beta = -0.72 (-1.38, -0.06), p<0.031). The chance of performing self-care decreased with increasing age (OR = 0.93 (0.89, 0.97), p<0.003). On the other hand, patients with a permanent partner had a higher chance of performing self-care (OR = 3.46 (1.27, 9.46), p<0.015). Conclusion: aspects related to the increase or decrease of self-care in patients living with human immunodeficiency virus were evidenced. However, further studies are necessary to emphasize the analytical character of the self-care of these patients.
Keywords: Self Care; Acquired Immunodeficiency Syndrome; HIV; Nursing Care; Adult Health; Ambulatory Care